The Effects of L-Arginine Supplementation on Oxygen Saturation and Blood Lactic Acid on the Physical Fitness Level of Muaythai Athletes in West Kalimantan - Bawana Mukti, Ibrah Fastabiqi; Jayadi; Heri Purnama Pribadi; Dhoni Akbar Ghozali; Agam Akhmad Syaukani; Muh. Isna Nurdin Wibisana; Herdianty Kusuma Handari (Journal of Physical Education Health and Sport, 2024)
This study aims to determine the extent of the effect of L-Arginine amino acid supplementation on oxygen saturation and lactic acid levels at the fitness level (VO2Max) of West Kalimantan muaythai athletes. High lactic acid levels can be an indicator of fatigue in athletes after undergoing a physical fitness test. This type of quantitative descriptive research used a randomized group pretest-posttest group design sampling method. The subjects in the study used were male athletes on the West Kalimantan Muaythai team who will be prepared for the 2024 International Student Muaythai Championship. In this study, the subjects were divided into two groups, the first group was given a placebo and the second group was given the amino acid L-arginine. Each group was given the same treatment, namely a physical fitness test to determine the VO2Max level using a bleep test. Before and after carrying out the physical fitness test, the subjects were checked for oxygen saturation, and blood lactic acid samples were taken. The results showed that L-Arginine supplementation had a positive effect in helping to maintain optimal oxygen saturation in the body and reducing the accumulation of blood lactic acid levels that can cause fatigue in Muay Thai athletes. This shows the significant role of L-arginine supplementation in helping to enhance physical endurance performance and speed up recovery during and after physical activity.